Moderasi Beragama dalam Kurikulum Pendidikan Agama Islam: Analisis Perspektif dan Implementasi - Isnaini; Fathurrahman Muhtar; Ismail Thoib (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the concept of religious moderation in the Islamic Religious Education (PAI) curriculum, examine its implementation, and identify challenges and strategies for its integration into the learning process. This study uses a qualitative approach with library research, through a review of various literature sources in the form of books, scientific journals, and relevant policy documents. The results show that religious moderation is an important concept that emphasizes balance, tolerance, and justice in religious life. Conceptually, the values of religious moderation have been integrated into the PAI curriculum in Indonesia, both in objectives, materials, and educational policy directions. However, its implementation still faces various challenges, such as limited teacher competency, the dominance of cognitive-oriented learning methods, the influence of digital media, lack of social environmental support, and an evaluation system that is not optimal in measuring affective aspects. To overcome these challenges, a comprehensive strategy is needed, including strengthening the values-based curriculum, developing innovative and dialogical learning methods, improving teacher competency, establishing an inclusive school culture, and the positive use of digital technology. Thus, the integration of religious moderation into the Islamic Religious Education curriculum is expected to shape students who not only possess sound religious understanding but also moderate, tolerant attitudes, and are able to live harmoniously in a pluralistic society.